The false friend : a novel - Goldberg, Myla. (New York : Doubleday, 2010)
Celia and Djuna ruled their clique of friends, but when Djuna disappeared while walking home together, Celia buried the truth. Now, twenty years later, Celia returns to her hometown to confess her sins.
Keywords: Schoolgirls -- Fiction; Female friendship -- Fiction; Deception -- Fiction; Memory -- Fiction; Children -- Death -- Fiction; New York (State) -- Fiction; Psychological fiction